The Inclusion of Children with Autistic Spectrum Disorder in Primary Schools (Bridging Cultures, 2023)
Autism is a disorder which affects the child's ability to communicate with those around them and develop mutual relations with them. Over the past twenty years, there has been a significant surge in the enrollment of students with autism in mainstream schools. This has created tensions and challenges in schools as staff struggle to meet these students and their families’ unique needs. Previous studies have revealed a lack of knowledge among school personnel regarding the distinctive traits and requirements of students with autism, as well as the effective practices necessary to support these students in inclusive educational environments. Therefore, finding a suitable method to communicate with kids and make practice the required duties are an essential concern. Teachers should be provided with appropriate training on autism spectrum disorder (ASD) so that they can successfully integrate a child with special needs in the classroom setting since a more knowledgeable teacher is more comfortable with inclusion.
Keywords: autism, pedagogical strategies, education, restricted interests, repetitive interests